2007
DOI: 10.1186/1477-9560-5-9
|View full text |Cite
|
Sign up to set email alerts
|

Deep venous thrombosis in the antenatal period in a large cohort of pregnancies from western India

Abstract: Background: Deep venous thrombosis (DVT) is an important complication in the peripartal and postpartal period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 26 publications
2
30
0
Order By: Relevance
“…The small number of controls also does not allow an estimation of relative risks of different thrombophilia in the occurrence of VTE during pregnancy, which will require a large population screening. Another limitation is that some other known – but less common – thrombophilia, such as factor XIII V34L, plasminogen activator inhibitor-1, endothelial PC receptor polymorphisms, were not included in the present study [36,40,41]. Recent studies also discovered new gene variants CYP4V2, SERPINC1, GP6 HIVEP1 locus and von Willebrand factors, which will be worth pursuing for future study [42,43,44,45].…”
Section: Discussionmentioning
confidence: 99%
“…The small number of controls also does not allow an estimation of relative risks of different thrombophilia in the occurrence of VTE during pregnancy, which will require a large population screening. Another limitation is that some other known – but less common – thrombophilia, such as factor XIII V34L, plasminogen activator inhibitor-1, endothelial PC receptor polymorphisms, were not included in the present study [36,40,41]. Recent studies also discovered new gene variants CYP4V2, SERPINC1, GP6 HIVEP1 locus and von Willebrand factors, which will be worth pursuing for future study [42,43,44,45].…”
Section: Discussionmentioning
confidence: 99%
“…The pathogenesis of many diseases during pregnancy is believed to be related with thrombosis or prothrombosis, for example fetal growth restriction, spontaneous abortions, and preeclampsia [2][3][4]. And venous thromboembolism (VTE), comprising deep vein thrombosis (DVT) and pulmonary embolism (PE), remains a leading cause of maternal death, causing 1.2-4.7 deaths per 100,000 pregnancies [5,6]. Recently, studies have suggested that hypercoagulability occurs in normal and pathologic pregnancies, with differences between them.…”
Section: Introductionmentioning
confidence: 99%
“…In a small series Cakmak et al, [13] found prothrombotic risk factors positive in 75% of CVT patients with CVT and in this study 38% of patients had multiple factors. Vora et al, [14] studied antenatal women with deep venous thrombosis and found 68% having two or more thrombophilic risk factors. This study showed association between some of the hereditary and acquired prothrombotic states and pregnancy associated deep vein thrombosis (DVT).…”
Section: Discussionmentioning
confidence: 99%